The Influence of Entrepreneurial Knowledge and Implementation of Business Center Activities on the Entrepreneurial Interest of Grade XI Students of the Marketing Department of SMK NEGERI 1 MEDAN - Hutapea, Dolse Maria; Agusti, Ivo Selvia (Lembaga Riset Mutiara Akbar (LARISMA), 2025)
This study aims to analyze the influence of entrepreneurial knowledge and the implementation of business centre activities on the entrepreneurial interest of eleventh-grade marketing students at SMK Negeri 1 Medan. A quantitative approach with an ex post facto design was employed, involving 63 respondents selected through total sampling. Data were collected using multiple-choice tests and questionnaires, then analyzed using multiple linear regression. The results show that: (1) Entrepreneurial knowledge and business centre activities simultaneously have a positive and significant influence on entrepreneurial interest (F = 30.790; sig = 0.001); (2) Entrepreneurial knowledge has a significant partial effect on entrepreneurial interest (t = 2.737; sig = 0.008); (3) Business centre activities also have a significant influence on entrepreneurial interest (t = 2.563; sig = 0.013). The coefficient of determination (R²) indicates that these variables contribute 50.6% to entrepreneurial interest. These findings highlight the importance of integrating entrepreneurial education with hands-on practice through school business centres to enhance students’ readiness to become young entrepreneurs.